INVENTARISASI IKAN-IKAN FAMILI BAGRIDAE DARI SUNGAI KAMPAR KIRI PROVINSI RIAU - Rowasti Simangunsong; Roza Elvyra (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
The Kampar Kiri River is a stream of the Kampar River which has a role as a fresh fish resource, generally the fish species found are consumption fish so that this river becomes one of the centers of fishery production in Riau as well as transportation, bathing, washing toilets, agriculture and house waste disposal. stairs. This greatly affects the availability of fish resources in the Kampar Kiri River, one of which is the Bagridae family. Available data and complete information, as well as continuous data collection from year to year regarding the types of Bagridae family fish in the waters of the Kampar Kiri River are still very lacking, so it is necessary to conduct research on the inventory of the Bagridae family fish in the Kampar Kiri River. The purpose of this study was to determine the diversity of the Bagridae family fish in the waters of the Kampar Kiri River, Pekanbaru, Riau Province. Fish samples were collected from local fishermen from January to November 2018. Fish were identified in the Zoology Laboratory of the Biology Department, Riau University. The fish found consisted of 5 species and 2 genera, namely the genus Bagroides and Mystus, B. melanopterus (25) individuals, M. nigriceps (65) individuals, M. nemurus (27) individuals, M. micracanthus (60) individuals, M. wyckii. (1) individual.